Lakeshore Christmas - Wiggs, Susan (Don Mills, Ont. : Mira, 2009)
When Maureen Davenport, a prim and proper librarian, is forced to direct Avalon's annual holiday pageant with Eddie Haven, a recovering former child star who hates Christmas with a passion, she prays for a Christmas miracle.
Keywords: Christmas -- Fiction; Love stories